(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper presents a comprehensive exploration of the phytochemical composition of flaxseed oil, highlighting its abundance in bioactive compounds such as lignans, antioxidants, and omega-3 fatty acids. These constituents contribute to the oil’s notable anti-inflammatory, antioxidant, and cardiovascular benefits. The review endeavors to narrow the divide between traditional medicine and contemporary scientific understanding by investigating the therapeutic potential of flaxseed oil. Through an examination of historical uses and traditional knowledge, the study seeks to establish a connection between ancient wisdom and current research. The paper evaluates the existing scientific evidence supporting the role of flaxseed oil in the treatment and prevention of various diseases. By delving into ongoing clinical trials and emerging research trends, the study offers insights into the evolving landscape of therapeutic applications for flaxseed oil. The synthesis of traditional medicinal practices with modern scientific findings underscores the versatility of flaxseed oil in promoting preventative and therapeutic healthcare strategies. This review aims to contribute to the growing body of knowledge surrounding flaxseed oil, advocating for its integration into mainstream healthcare practices based on its holistic potential.